Studies on the Effect of IBA - Chemical Formulations on Rooting Behaviour of Hippophae salicifolia D. Don Cuttings - Shamet, G.S.; Naveen, C.R. (Indian Journal of Agroforestry, 2020)
Adapted to inner dry temperate regions of Himalaya between 3000-4300 m elevations. The species survive extreme temperature of -60Â°C to 40Â°C and at the same time provide wide array of products like food, fuel, fodder, fertilizer, cosmetics, medicines, beverages and timber to the locals besides helping in soil and water conservation in the fragile mountaneous lands. Keeping in view the economic and ecological potential, a study was undertaken to assess the rooting behaviour of Hippophae salicifolia - a potential agroforestry species of the dry cold deserts of Himalaya. Application of 0.4% IBA formulation (in talc) produced significantly maximum rooting of 73.33 per cent and 56.67 per cent, respectively in monsoon and spring season under Solan (Nauni) conditions. Similarly, a high initial level of total phenol, sugar, starch and carbohydrate content seemed to favour rooting in the species.